Development of a Non-Invasive Blood Glucose Measurement Device Using the Wheatstone Bridge Method Based on Arduino - Huamaidillah Kurniadi Wardana; Vincent Andrew Akpan; Mohamed Bakry El Mashade; Bidya Debnath; Anderson L. Silva (Tinta Emas Publisher, 2024)
Monitoring blood glucose levels in the body of Diabetes Mellitus (DM) patients regularly is an essential part of managing blood sugar levels, which can improve the quality of life for DM patients. One approach in health technology for non-invasive blood glucose detection is through the use of the patient's urine. In this study, a blood glucose measurement device was designed using Arduino Uno, a Wheatstone bridge circuit, a voltage amplifier, and a 16x4 LCD to display the measurement results. The measurement process involves placing a urine sample on one arm of the Wheatstone bridge circuit, where two copper electrode cells are positioned. Changes in the output voltage of the bridge circuit result in a voltage variation, which is then amplified by the voltage amplifier, allowing it to be read by the Arduino. The measurement results indicate that the Wheatstone bridge method can be used to detect glucose in urine, with changes in voltage observed for each tested urine sample.